The Influence of Ethical Information Technology Use and Green Computing Awareness on Green Digital Behavior: Evidence from the Government of West Sulawesi Province, Indonesia - Nurmala Daeng Kanang; Hari Yeni; Usman (ADMAN: Journal of Contemporary Administration and Management, 2026)
The rapid digital transformation of public administration has improved organizational efficiency while simultaneously increasing concerns regarding the environmental sustainability of information technology utilization. Although governments continue to expand digital governance initiatives, limited attention has been devoted to understanding the behavioral factors that encourage environmentally responsible digital practices among public employees. This study investigates the influence of Ethical Information Technology Use and Green Computing Awareness on Green Digital Behavior among employees of the Government of West Sulawesi Province, Indonesia. This research employed a quantitative explanatory approach using a structured questionnaire distributed to 120 State Civil Apparatus (ASN) selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement model and the structural relationships among the proposed constructs. The findings reveal that both Ethical Information Technology Use and Green Computing Awareness have positive and significant effects on Green Digital Behavior. Green Computing Awareness demonstrates the strongest influence, indicating that employees' understanding of environmentally sustainable computing practices is a key determinant of responsible digital behavior. The structural model explains 58.8% of the variance in Green Digital Behavior, suggesting satisfactory predictive capability. The study contributes to the Green Information Systems literature by extending existing research beyond technological adoption toward individual behavioral determinants within public organizations. The findings also provide empirical support for the Theory of Planned Behavior by demonstrating that employees' ethical responsibility and environmental awareness encourage environmentally sustainable digital practices. From a practical perspective, the study recommends integrating Green IT education, environmental awareness programs, and ethical technology policies into digital government initiatives to support sustainable digital governance.